Information seeking behaviour of research scholars in the digital environment of a multidisciplinary institution - Ali, Amjad; Hasan, Fatima (Qualitative and Quantitative Methods in Libraries; Vol 6 No 4 (2017): December 2017 Issue, 2019)
ICT has changed the environment of learning at all levels of education, influencing the information-seeking process and behaviour of users in almost all disciplines of study. This study presents a survey on the users of digital resources in a multidisciplinary institution which has been conducted in order to assess the information seeking behaviour of research scholars, their preference and views on the digital resources and services being provided, requirements and suggestions for further improvement of the services.  This study has been conducted on the clientele of the Digital Resources Centre (DRC) of the Aligarh Muslim University Library. The University was established about 150 years ago and is now one of the largest universities of India offering courses of study in almost all disciplines of knowledge through more than a hundred developed departments. The university has been rated as the second best in the country by the Times Higher Education Asia Ranking for the last two consecutive years.   The Library witnessed a sea change in its role as information provider and leader in the country after the digitization drive of contents, networking of its departments and subscription of electronic databases and has been declared as the best amongst all Indian universities libraries during 2015 by the visiting team of the National Accreditation and Assessment Council of Government of India.  The digitized contents are made available to the academic community through DRC which is a central facility for proving access to over 30,000 users through 10,000 odd computers to access over 55 million e-books, 7 million e-journals and an equal amount of electronic theses and dissertations besides a large number of reference tools and audiovisual resources. DRC has a provision for accommodating 100 students at a time on separate computers which facilitates a higher speed of information retrieval through Linux. Being located in the centre of the University and surrounded by the departments of arts, social sciences, sciences, natural sciences, commerce, theology, business management etc, DRC works as a central facility and a natural choice for the information seekers, mainly the academic and research community of the University.  The main objectives of the study have been to (a) study the information seeking behaviour of M. Phil.  and Ph. D. students of the Aligarh Muslim University; (b) know about the personal preferences in context of the facilities being provided in DRC; (c) assess their levels of satisfaction of users with the available digital resources and services; (d) develop and improve the existing facilities based on the feedback received from researchers; and propose a model of DRC for the other institutions.  Information from the respondents was collected through an open-ended questionnaire asking questions on various aspects including procedures, problems and future prospects of the services being offered. Copies of the questionnaire were evenly distributed to the students of M. Phil. and Ph.D. courses asking about their subjects of studies, frequency, purpose and preferred time of visit, level of satisfaction with the resources and technical support provided to them. The respondents were also invited to suggest ways for improving the services of DRC. Duly filled up questionnaires were received from 50 respondents and the data so received was analyzed and presented in tables and charts. The respondents participated in the survey belong to the humanities and social sciences (66%), commerce and business management (10%), sciences (8%) and engineering and medicine (16%).  It has been found that most of the visitors prefer morning time for research work and visit DRC daily. The main purpose of their visit is to write research papers and theses. It has also been found that 98% of the respondents are satisfied with the digital resources being offered through DRC while very few researchers are not aware of the existing facilities. The suggestions received from the users reveal emphasis on the extension in the opening time, availability of more databases and software for data analysis, however some of them have suggested scanning and printing facilities to be provided within the DRC.